2017
DOI: 10.1093/femsle/fnx125
|View full text |Cite
|
Sign up to set email alerts
|

Quick change: post-transcriptional regulation in Pseudomonas

Abstract: Pseudomonas species have evolved dynamic and intricate regulatory networks to fine-tune gene expression, with complex regulation occurring at every stage in the processing of genetic information. This approach enables Pseudomonas to generate precise individual responses to the environment in order to improve their fitness and resource economy. The weak correlations we observe between RNA and protein abundance highlight the significant regulatory contribution of a series of intersecting post-transcriptional pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 74 publications
0
40
0
Order By: Relevance
“…Sophisticated regulatory networks in Pseudomonads control the physiological responses to these stressful conditions, including both local and global regulators that adjust transcriptional levels according to environmental cues (Tribelli et al, 2013;Balasubramanian et al, 2015;Arce-Rodríguez et al, 2016;Udaondo et al, 2018). Carbon catabolite repression, governed by the Crc protein, is a major player among these regulatory systems in Pseudomonas species (Wolff et al, 1991;Collier et al, 1996;Velázquez et al, 2004;Rojo, 2010;Grenga et al, 2017;Liu et al, 2017;Wirebrand et al, 2018). Crc is a global regulator that exerts its influence at the post-transcriptional level by binding (together with the Hfq protein, the actual RNA-binding protein in the complex) a cognate region of target mRNAs (Kambara et al, 2018), thus blocking translation (Moreno et al, 2009;Milojevic et al, 2013;Moreno et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sophisticated regulatory networks in Pseudomonads control the physiological responses to these stressful conditions, including both local and global regulators that adjust transcriptional levels according to environmental cues (Tribelli et al, 2013;Balasubramanian et al, 2015;Arce-Rodríguez et al, 2016;Udaondo et al, 2018). Carbon catabolite repression, governed by the Crc protein, is a major player among these regulatory systems in Pseudomonas species (Wolff et al, 1991;Collier et al, 1996;Velázquez et al, 2004;Rojo, 2010;Grenga et al, 2017;Liu et al, 2017;Wirebrand et al, 2018). Crc is a global regulator that exerts its influence at the post-transcriptional level by binding (together with the Hfq protein, the actual RNA-binding protein in the complex) a cognate region of target mRNAs (Kambara et al, 2018), thus blocking translation (Moreno et al, 2009;Milojevic et al, 2013;Moreno et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The complex network of transcriptional regulators and sigma factors guarantees fine-tuned regulation of the optimized geneexpression-based systems in the opportunistic pathogen. However, recent studies also indicated that a number of post-transcriptional regulatory processes are responsible for changes in the protein profile and the phenotype (Martínez and Vadyvaloo, 2014;Krueger et al, 2016;Little et al, 2016;Ouidir et al, 2016;Grenga et al, 2017). In this study, we obtained extensive proteome datasets under several different environmental conditions that in their entirety allowed a comparison of RNA to protein ratios for each individual gene.…”
Section: Introductionmentioning
confidence: 99%
“…In response to environmental stimuli, GacS phosphorylates and activates of the response regulator GacA leading to the upregulation of the expression of regulatory small RNAs. These sRNAs bind to the global regulator RsmA, releasing its repression of genes necessary for biofilm formation 20,40 . The decrease in biofilm formation observed upon CRISPRimediated silencing of gacS is in agreement with the regulatory model and with phenotypes observed in gacS mutants in various Pseudomonas 17,18,25,40,68 .…”
Section: Discussionmentioning
confidence: 99%
“…These sRNAs bind to the global regulator RsmA, releasing its repression of genes necessary for biofilm formation 20,40 . The decrease in biofilm formation observed upon CRISPRimediated silencing of gacS is in agreement with the regulatory model and with phenotypes observed in gacS mutants in various Pseudomonas 17,18,25,40,68 . In SBW25, GacS is also regulating genes involved in oxidative stress response, and the gacS::Tn5 mutant has a reduced capacity to survive exposure to sub-lethal doses of H2O2 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation